Penggunaan Alat Pelindung Diri (Handscoon) Sebagai Upaya Dalam Pencegahan Infeksi Nosokomial Di Rumah Sakit Sumber Kasih Kota Cirebon - Herlina; Ahmad Syaripudin; Pujiyana; Ira Rahayu Okta; Lalu Rahmatullah Hidayat (Awatara Publisher, 2024)
The hospital is a place for providing health services that have quality in accordance with predetermined standards, one of which is by carrying out infection prevention and control (PPI) efforts. The purpose of this study was to determine the prevention of nosocomial infections from the use of personal protective equipment (PPE). The method in this study uses a qualitative approach with case studies as the main method. Data collected through interviews, documentation, analysis. The results of the SWOT analysis of the availability of personal protective equipment in hospitals, nurse motivation are very influential in infection prevention, discipline and awareness of officers are influenced by the length of work. It can be concluded in this study, that the prevention of nosocomial infections is closely related to nurses' compliance in the use of personal protective equipment (PPE) as a form of compliance, discipline, and protection from infections in the hospital